解方程 x(2x-5)-x(x+2)=x²-6
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 01:03:22
解方程x(2x-5)-x(x+2)=x²-6解方程x(2x-5)-x(x+2)=x²-6解方程x(2x-5)-x(x+2)=x²-6x(2x-5)-x(x+2)=x
解方程 x(2x-5)-x(x+2)=x²-6
解方程 x(2x-5)-x(x+2)=x²-6
解方程 x(2x-5)-x(x+2)=x²-6
x(2x-5)-x(x+2)=x²-6
2x²-5x-x²-2x=x²-6
-7x=-6
x=6/7
如果不懂,请追问,祝学习愉快!
x(2x-5)-x(x+2)=x^2-6 2x^2+5x-x^2-2x=x^2-6 3x=-6 x=-2
解方程x/(x-2)=2x/(x-3)+(1-x)/(x-5x+6)
2X(x+1.5x)=5x 解方程
解方程;x/x-4=5x/x-2
解方程 x(2x-5)-x(x+2)=x²-6
解方程:2(X-3)(X+5)=X平方+(X+2)(X-2)+(X+7)
解方程:(x-2)(x^2-6x-9)=x(x-5)(x-3)
解方程(x-3/x)-(3-x/x+1)=5x-15/2x+2
5x(x+7)(x+4)=5x(x^2+11X)解方程,
解方程 x(2x-4)+3x(x-1)=5x(x-3)+8
解方程:x(3x-4)+2x(x+7)=5x(x-7)+90
解方程 3x/x×x-1+x×x-1/3x=5/2
解方程(x+1/x+2)-(x+2/x+3)=(x+5/x+6)-(x+6/x+7)
解方程(x-6)(x^2+x+1)-x(x+1)(x-1)=x(2-5x)
解方程:x+2/x+1-x+3/x+2=x+6/x+5-x+7/x+6
解分式方程:(x+1)/(x+2)+(x+6)/(x+7)=(x+2)/(x+3)+(x+5)/(x+6)
解分式方程: (x-1)/(x-2)+(x-6)/(x-7)=(x-2)/(x-3)+(x-5)/(x-6)
解方程:(x+3)/(x+2)-(x+4)/(x+3)=(x+5)/(x+4)-(x+2)/(x+1)
解方程 x+2/x+1+x+8/x+7=x+6/x+5+x+4/x+3